Health Justice and Indigenous Food Sovereignty: The Case for Traditional Dietary Practices in Indonesia (Indonesian Health Justice Review, 2025)
Food sovereignty plays a crucial role in health justice, particularly for indigenous communities in Indonesia who have maintained traditional dietary practices for generations. This paper explores the relationship between health justice and indigenous food sovereignty, focusing on how traditional food systems contribute to health and well-being while also addressing the challenges posed by the modernization of food production and consumption. Using a combination of ethnographic fieldwork, interviews with indigenous community members, and a review of national agricultural and health policies, the research examines the decline of traditional diets in favor of processed foods and the resultant health consequences, including malnutrition, obesity, and chronic diseases. The study argues that promoting indigenous food sovereignty, which respects local food systems and cultural practices, is essential for achieving health justice. By advocating for policies that protect and revitalize traditional food systems, the paper highlights the importance of food security, sustainability, and culturally appropriate nutrition in improving health outcomes for indigenous populations. The research concludes by recommending a more integrated approach to health policy that incorporates indigenous knowledge, supports local agricultural practices, and fosters greater recognition of traditional diets as part of Indonesia’s broader public health strategies.